Associations of maternal insulin sensitivity during pregnancy with childhood central adiposity in the Genetics of Glucose regulation in Gestation and Growth (Gen3G) cohort. Issue 2 (11th October 2022) - Ghildayal, Nidhi; Allard, Catherine; Blais, Kasandra; Doyon, Myriam; Arguin, Melina; Bouchard, Luigi; Perron, Patrice; Hivert, Marie‐France
Summary: Background: Childhood obesity has been associated with prenatal exposure to maternal hyperglycaemia, but we lack understanding about maternal insulin physiologic components that contribute to this association. Objectives: Evaluate the association between maternal insulin sensitivity during pregnancy and adiposity measures in childhood. Methods: In 422 mother–child pairs, we tested associations between maternal insulin sensitivity measures at ~26 weeks of pregnancy and child adiposity measures, including dual‐energy X‐ray absorptiometry body composition and anthropometry (body mass index and waist circumference) at ~5 years. We used linear regression analyses to adjust for maternal age, ethnicity, gravidity, first‐trimester body mass index, and child sex and age at mid‐childhood. Results: In early pregnancy, maternal mean age was 28.6 ± 4.3 years and median body mass index was 24.1 kg/m 2 . Lower maternal insulin sensitivity indices were correlated with greater child adiposity based on anthropometry measures and on dual‐energy X‐ray absorptiometry total and trunk % fat in univariate associations (r = −0.122 to −0.159). Lower maternal insulin sensitivity was specifically associated with higher dual‐energy X‐ray absorptiometry trunk % fat ( n  = 359 for Matsuda; β  = −0.034 ± 0.013; p  = 0.01) after adjustment for covariates, including maternal body mass index. Conclusions: Maternal insulin sensitivity during pregnancy may contribute to increased risk for higher offspring central adiposity in middle childhood.